2009
DOI: 10.1111/j.1398-9995.2008.01876.x
|View full text |Cite
|
Sign up to set email alerts
|

Additive role of tiotropium in severe asthmatics and Arg16Gly in ADRB2 as a potential marker to predict response

Abstract: As many as 30% of severe asthmatics on conventional medications with reduced lung function were found to respond to adjuvant tiotropium. The presence of Arg16Gly in ADRB2 may predict response to tiotropium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 40 publications
0
58
1
4
Order By: Relevance
“…Probably, these differences are due to the mixture of our population, as demonstrated by the Fortes et al study 18 in which the Venezuelan Mestizo population with autoimmune hepatitis showed some disease-protective HLA alleles which differ from those reported for Caucasians and Japanese populations 18 . In several meta-analysis published [19][20][21][22] , the authors concluded that genetic polymorphisms of ADRβ2 do not represent an increased risk for developing asthma, yet are important in therapy outcome. In patients with severe asthma, Park et al 22 , showed an association between Arg/Gly polymorphism at codon 16 of ADRβ2 and better response to tiotropium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Probably, these differences are due to the mixture of our population, as demonstrated by the Fortes et al study 18 in which the Venezuelan Mestizo population with autoimmune hepatitis showed some disease-protective HLA alleles which differ from those reported for Caucasians and Japanese populations 18 . In several meta-analysis published [19][20][21][22] , the authors concluded that genetic polymorphisms of ADRβ2 do not represent an increased risk for developing asthma, yet are important in therapy outcome. In patients with severe asthma, Park et al 22 , showed an association between Arg/Gly polymorphism at codon 16 of ADRβ2 and better response to tiotropium.…”
Section: Discussionmentioning
confidence: 99%
“…In several meta-analysis published [19][20][21][22] , the authors concluded that genetic polymorphisms of ADRβ2 do not represent an increased risk for developing asthma, yet are important in therapy outcome. In patients with severe asthma, Park et al 22 , showed an association between Arg/Gly polymorphism at codon 16 of ADRβ2 and better response to tiotropium. Probably, our asthmatic population would respond better to anticholinergic agents since this polymorphism is the most prevalent 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Показано, что ответ на тиотропий ассоциирован с наличием Arg16Gly полиморфизма гена β2 адренорецептора и наличие этого полимор физма может быть предиктором ответа на тиотро пий [36]. В РКИ [6] была проверена гипотеза, что ти отропий может быть альтернативой ДДБА у больных с не контролируемой иГКС персистирующей БА, имеющих гомозиготный генотип Arg16Arg.…”
Section: ограничения по применению ддбаunclassified
“…56 Another study of 138 severe asthmatics with reduced pulmonary function found that the addition of tiotropium bromide to conventional asthma medications resulted in an increase in FEV 1 exceeding 15% in 33% of the patients. 57 A systematic review found that it may have a beneficial role in moderate -to -severe asthma, and there were no safety concerns.…”
Section: Future Therapies Long -Acting Anticholinergic Agentsmentioning
confidence: 99%